Objective and Subjective Long-Term Outcome of Pelvic Fractures Treated Conservatively in Cats - Tinoco, Isis Alexandra Pincella [UNESP]; Rahal, Sheila Canevese [UNESP]; De Siqueira Silva Junior, Jose Ivaldo [UNESP]; Da Silva, Jeana Pereira [UNESP]; Juliano, Lara Cristina Bastos [UNESP]; Kano, Washington Takashi [UNESP]; Mamprim, Maria Jaqueline [UNESP] (My University, 2024)
This study aimed to evaluate the long-term outcome of cats with pelvic fractures treated conservatively using objective and subjective methods. Twenty client-owned cats were assessed: Group 1 (G1)-ten cats with pelvic fractures treated conservatively, and group 2 (G2)-ten healthy cats. The time point of the evaluation of G1 cats was a mean of 45.6 months after the trauma. The visual lameness scoring revealed that 70% of the cats in G1 had no lameness and 30% had low-grade lameness. Pain on palpation of the pelvis was observed in 80% of these cats. The owner's answers to the questionnaire for the assessment of the quality of life were classified as an excellent outcome in 80% of the cats and a good outcome in two cats. Regarding the objective data collected using a pressure-sensitive walkway, seven cats had a symmetry index of the peak vertical force above the cutoff value, based on G2. The pain degree on palpation of the pelvis revealed a strong correlation with lameness degree and a moderate correlation with symmetry index for peak vertical force of the hind limbs. The questionnaire pain answered by the owner did not correlate with lameness degree, pain degree on palpation, or symmetry index for peak vertical force of the hind limbs. Cats with pelvic fractures treated conservatively had an excellent outcome in 80% of the cases by subjective analysis of the owners' questionnaire; however, 70% showed changes by the objective analysis based on the symmetry index.
Keywords: Feline; kinetic; pressure-sensitive walkway; questionnaire